Effect of sorbitan ester structure on the separation between tetrahydrofuran and water - Bartokova, Bibiana; Marangoni, Alejandro G.; Laredo, Thamara; Pensini, Erica (Frontiers in Soft Matter, 2023)
This study separates tetrahydrofuran (THF)-water mixtures containing varying THF percentages, using sorbitan esters (Spans) with different tail characteristics. We probe the separation mechanisms using attenuated total reflectance-Fourier transform infrared spectroscopy and small angle X ray scattering (SAXS). THF and water are miscible and interact through hydrogen bonds. Water splits the COC absorbance band of THF into a peak at ≈1070 cm -1 (crystalline THF) and a dominant peak at ≈1050 cm -1 (glassy THF), indicating disorder. Depending on the Span, separation occurs for mixtures containing up to 70% THF (v/v, relative to water). Spans with unsaturated tails separate the lowest THF percentages. Tail length and number of Span tails enhances ordering of THF, and the crystalline THF peak at ≈1070 cm -1 dominates. Spans interact with THF through hydrogen bonds, as reflected in the splitting of the COC band of THF. Furthermore, C-H…O hydrogen bonds cause a blueshift in the νas(CH2) band of Spans with increasing THF. This effect is most significant in Span 40 and 60, indicating that they interact with THF more strongly than Span 20, Span 80 and Span 85. In contrast, they interact with water less strongly than Span 20, Span 80 and Span 85, as indicated by their flocculation at low THF percentages. Therefore, we propose that separation between THF and water occurs primarily through two mechanisms: 1) Span 20, Span 80 and Span 85 compete against THF for interactions with water through their hydrophilic head, and 2) Span 40 and Span 60 preferentially interact with THF through their tails. Nonetheless, water also interacts with the heads of Span 40 and Span 60, as indicated by SAXS. SAXS shows that in THF Spans self-assemble into micelles, which aggregate into either surface fractals or mass fractals. There are two persistence lengths because of the limited order in THF. Water orders self-assembled structures, likely by favoring the formation of micelles which host water in their interior. Therefore, we identify a single persistence length (≈ 25 Å), representative of the distance between the micelle centers.